Manutenção preditiva: avaliação de equipamento rotativo - SANTOS, Wakesson da Silva (176, 2024)
Este estudo se propõe a explorar a aplicação da análise de vibração na manutenção preditiva de mancais de exaustores, investigando sua eficácia na detecção precoce de falhas, otimização de intervenções e no aumento da confiabilidade operacional. Ao compreender os padrões vibratórios associados ao funcionamento normal e às diferentes modalidades de falha, busca-se contribuir para o aprimoramento das práticas de manutenção preventiva em ambientes industriais, promovendo uma gestão mais eficiente dos recursos e reduzindo custos associados a paradas não programadas.

Predictive maintenance has emerged as a critical strategy to maximize operational availability and extend the lifespan of industrial equipment. Among the various techniques employed, vibration analysis has emerged as a powerful tool for monitoring the condition of rotating machinery, such as bearings. This study aims to explore the application of vibration analysis in the predictive maintenance of exhaust fan bearings, investigating its effectiveness in early fault detection, intervention optimization, and enhancing operational reliability. By understanding the vibrational patterns associated with normal operation and different failure modes, the study seeks to enhance preventive maintenance practices in industrial settings, promoting more efficient resource management and reducing costs associated with unplanned downtime.
Predictive maintenance: assessment of rotating equipment
Keywords: Administração de manutenção de fábricas e equipamentos; Manutenção preditiva; Controle e Processos Industriais